Cardiovascular Effects of Continuous Dexmedetomidine Infusion Without a Loading Dose in the Pediatric Intensive Care Unit. (December 2015) - Cummings, Brian M.; Cowl, Allison S.; Yager, Phoebe H.; El Saleeby, Chadi M.; Shank, Erik S.; Noviski, Natan
Background: Use of dexmedetomidine in pediatric critical care is common, despite lack of prospective studies on its hemodynamic effects. Objective: To describe cardiovascular effects in critically ill children treated with a constant continuous infusion of dexmedetomidine without a loading dose at highest Food and Drug Administration-approved adult dose. Methods: Prospective, pilot study of 17 patients with dexmedetomidine infused at a rate of 0.7 μg/kg/h for 6 to 24 hours. Heart rate (HR) and blood pressure (BP) values over time were analyzed by a random effects mixed model. Results: Patients with median age of 1.6 years (1 month to 17 years) and median weight of 11.8 kg (2.8-84 kg) received an infusion for a mean of 16 ± 7.2 hours. There were no cardiac conduction abnormalities. One patient required discontinuation of infusion for predetermined low HR termination criteria at hour 13 of infusion; there was no clinical compromise and it coincided with planned extubation. Decreased HR of 20% from baseline was found in 35% of patients. The mean HR reduction was largest at hour 13 of infusion with a decrease of 13 ± 17 bpm from baseline, but HR changes over time were not statistically significant. Blood pressure effects included a decrease in 12% and an increase in 29%. There was a small but statistically significant increase in systolic BP of 0.4 mm Hg/h of infusion, P < .001. Conclusion: A continuous infusion of 0.7 μg/kg/h of dexmedetomidine without a loading dose for up to 24 hours in critically ill children had tolerable effects on HR and BP.